Pancasila as a Guide to the Behavior of the Young Generation Amidst Social Change (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
Pancasila plays a crucial role as a guideline for the behavior of the younger generation amidst the dynamics of social change driven by technological developments, globalization, and shifts in values ​​and culture. These rapid changes require the younger generation to adapt without losing their identity and the moral values ​​that characterize the Indonesian nation. In this context, Pancasila serves as a moral foundation, ethical guide, and direction for action, thereby preventing character degradation and a weakening of national spirit. The noble values ​​of Pancasila, such as divinity, humanity, unity, democracy, and justice, serve as the foundation for developing positive, resilient, and integrity-based behavior in the younger generation. This study aims to analyze the extent to which Pancasila plays a role in shaping the behavior of the younger generation amidst complex social change and to identify efforts to strengthen Pancasila values ​​in everyday life. The results indicate that internalizing Pancasila values ​​through education, role models, and school culture can foster positive character and enhance national awareness.
Keywords: Pancasila; Young Generation; Social Change